The impact of squamous metaplasia in transitional cell carcinoma of the bladder - (:unkn) unknown (Kluwer Academic Publishers, 1991)
The authors report a case of squamous cell carcinoma of the bladder induced by radiation therapy for transitional cell carcinoma, possibly from sites of squamous metaplasia, which were present at the time of initial diagnosis. Although data in the literature are not sufficient at the moment in terms of implication on prognosis, foci of squamous metaplasia during the initial diagnosis of transitional cell carcinoma must be carefully sought and their presence warrants caution in utilizing irradiation in the management of the disease. © 1991 Akadémiai Kiadó.